Effect of Arthrospira Microalga Fortification on Physicochemical Properties of Yogurt - Wanida Pan-utai; Jariya Atkonghan; Tipakorn Onsamark; Wachiraya Imthalay (My University, 2020)
Arthrospira (Spirulina) platensis, a blue-green microalga, is a rich source of organic nutrients. Microalgae are used as food supplements with enhanced nutritional and functional values. Consumption of fermented milk products such as yogurt has recently increased. Both oven-dried and fresh Arthrospira biomass supplemented into yogurt at different concentrations of 0.1, 0.3, and 0.5% (w/v) and 1, 5, and 10% (v/v), respectively improved physicochemical properties. Arthrospira supplemented in yogurt fermentation gave faster decrease in pH value with green color index of finished yogurt. Oven drying is a convenient method; however, fresh biomass gave similar nutritional value with higher C-phycocyanin content. During storage, pH, titratable acidity, and color of yogurt showed negligible variations. Results indicated that Arthrospira increased both nutritional composition and functional properties of yogurt as a natural food ingredient.
Keywords: Arthrospira; Spirulina (dietary supplement); Ingredient; Functional food; Food composition data; Algal biology and biofuel production